Annual Plant Reviews Online 2018
DOI: 10.1002/9781119312994.apr0286
|View full text |Cite
|
Sign up to set email alerts
|

Sugar and Abscisic Acid Regulation of Germination and Transition to Seedling Growth

Abstract: The sections in this article areIntroductionABASignaling during Germination and Early Seedling GrowthSugar Signaling Represses Germination and the Transition to Vegetative GrowthConclusionsAcknowledgments

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…Sugars arrest early seedling establishment. It has been shown that this process is closely associated with plant hormone biosynthesis and signalling, in particular with that of ABA (for review see Finkelstein and Gibson, 2001;Gazzarini and McCourt, 2001;León and Sheen, 2003;Rook et al, 2006;Dekkers and Smeekens, 2007;Rognoni et al, 2007). Mutants that were insensitive to the inhibiting effect of glucose and sucrose on early seedling development were isolated by several groups and identified ABA deficient mutants (i.e.…”
Section: The Genetic Control Of Seed Storage Compounds Seed Deterioration and Early Seedling Developmentmentioning
confidence: 99%
“…Sugars arrest early seedling establishment. It has been shown that this process is closely associated with plant hormone biosynthesis and signalling, in particular with that of ABA (for review see Finkelstein and Gibson, 2001;Gazzarini and McCourt, 2001;León and Sheen, 2003;Rook et al, 2006;Dekkers and Smeekens, 2007;Rognoni et al, 2007). Mutants that were insensitive to the inhibiting effect of glucose and sucrose on early seedling development were isolated by several groups and identified ABA deficient mutants (i.e.…”
Section: The Genetic Control Of Seed Storage Compounds Seed Deterioration and Early Seedling Developmentmentioning
confidence: 99%